TRADISI NYEKAR MENJELANG HARI RAYA DI PONTIANAK, KALIMANTAN BARAT - Sri Wahyuni (Raheema, 2019)
Abstract: Study in islamic education psychology, tradition or style as a habit carried out by residents, especially in the Nyekar tradition or commonly known as the Grave Pilgrimage, is something that should be preserved especially before the holidays, especially in Pontianak. This tradition is carried out in order to offer prayers to those who have been previously, and as a reminder that the world is only temporary. Usually, the person who cleans the tomb, then shows it by reciting a prayer in front of him. The method used in this research is data.